Advance Funding for Infrastructure PPPs : Cautions from Two Road Projects in Peru - Kerf, Michel (World Bank Group, Washington, DC, 2015)
Public private partnerships (PPPs) for infrastructure projects require substantial initial funding that private operators in developing countries can rarely obtain in the domestic market. In 2005, in the context of two important road projects, the government of Peru introduced a financial innovation with two goals: improve the access of the projects’ concessionaires to the international financial markets and book government support as an operating expense rather than debt. The innovations offered distinct advantages to the concessionaires while imposing a significant burden on the government, which has since stopped using them. Nonetheless, the new approach can still be useful in carefully limited instances to help solve the funding problem.